2021
DOI: 10.3389/fmats.2021.762030
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Development of Sustainable PECVD Semitransparent Photovoltaics: A Review

Abstract: Energy is the driving force behind the upcoming industrial revolution, characterized by connected devices and objects that will be perpetually supplied with energy. Moreover, the global massive energy consumption increase requires appropriate measures, such as the development of novel and improved renewable energy technologies for connecting remote areas to the grid. Considering the current prominent market share of unsustainable energy generation sources, inexhaustible and clean solar energy resources offer t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 114 publications
(102 reference statements)
0
8
0
Order By: Relevance
“…Functional thin films deposited using plasma processes are commonly used for a wide range of applications from aerospace, automotive, biomedical, microelectronics, packaging, and more recently in renewable energy with the development of solar cells and perovskite coatings. [ 27 ]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Functional thin films deposited using plasma processes are commonly used for a wide range of applications from aerospace, automotive, biomedical, microelectronics, packaging, and more recently in renewable energy with the development of solar cells and perovskite coatings. [ 27 ]…”
Section: Resultsmentioning
confidence: 99%
“…Functional thin films deposited using plasma processes are commonly used for a wide range of applications from aerospace, automotive, biomedical, microelectronics, packaging, and more recently in renewable energy with the development of solar cells and perovskite coatings. [27] Traditionally, PECVD operating at low pressure has been extensively used to deposit functional films via the direct interaction of plasma species and an organic precursor. In recent years, several works have highlighted the possibility to use atmospheric pressure PECVD processes for surface functionalization through the deposition of various coatings by controlling precursor fragmentation in the discharge.…”
Section: Cleaning Of Aluminum and Thin Film Deposition For Protection...mentioning
confidence: 99%
“…70 polymer-based solar cells. 135 Hoye et al used NiO x as HTL and ZnO as ETL-capped BiOI absorber layer, while ITO was used as the conducting substrate (bottom electrode) and Al layer as the top electrode to form the so-called all-inorganic solar cells device (Fig. 9(b)).…”
Section: Bismuth Oxyiodide In Photovoltaic Technologymentioning
confidence: 99%
“…For instance, the previous report shows that the BiOI absorber layer could also be combined with the so-called hole/electron transport layer (HTL and ETL, respectively), wherein, in fact, this design is similar to that of organic-based solar cells, especially perovskite and polymer-based solar cells. 135 Hoye et al used NiO x as HTL and ZnO as ETL-capped BiOI absorber layer, while ITO was used as the conducting substrate (bottom electrode) and Al layer as the top electrode to form the so-called all-inorganic solar cells device (Fig. 9(b)).…”
Section: Bismuth Oxyiodide In Photovoltaic Technologymentioning
confidence: 99%
“…In spite of facing a set of challenges, plasma assisted thin film deposition systems receive a lot of attention for the development of thin films that are highly uniform, pinhole‐free along with reduced roughness. However, in order to have thin film properties of newly developed HP‐PECVD deposition system comparable to that of LP‐PECVD methods, a lot of tunings are needed, for instance, electrode geometry, sample injection technique, reactor pressure, source power and frequency because the plasma properties are highly influenced by pressure and operating frequency [31] . It is observed that a number of methods for the film deposition at high pressure employing different types of plasma sources due to their low cost because there is no need of expensive vacuum system along with relevant accessories.…”
Section: Introductionmentioning
confidence: 99%